2022
DOI: 10.1177/03635465221131281
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in the Evaluation of Male Versus Female Athletes in Sports Medicine Research: A Systematic Review

Abstract: Background: Female sports participation continues to rise; however, inequalities between male and female athletes still exist in many areas and may extend into medical research. Purpose: The purpose of this study was to (1) compare the number of published studies evaluating male versus female athletes in various sports and (2) identify which co-ed sports currently underrepresent female athletes in the sports medicine literature. Study Design: Systematic review; Level of evidence, 4. Methods: All nonreview rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Our findings that few studies included females or evaluated sex differences are well supported by prior literature demonstrating inequalities in research conducted on female versus male athletes 61. While some sports (eg, American football) are not widely practiced among both sexes, including both males and females in studies and evaluating sex differences when possible is essential and may have substantial clinical implications.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings that few studies included females or evaluated sex differences are well supported by prior literature demonstrating inequalities in research conducted on female versus male athletes 61. While some sports (eg, American football) are not widely practiced among both sexes, including both males and females in studies and evaluating sex differences when possible is essential and may have substantial clinical implications.…”
Section: Discussionsupporting
confidence: 80%
“…The impacts of COVID-19 have been far and wide, and have been felt more by women and girls in most industries. Sport has not been spared with girls dropping out of sport at higher rates than boys 1 and women and non-binary individuals being under-represented in broadcasting, 2 management 3 and sport science 4 (although we know those are not new issues! ).…”
Section: Narrowing the Gap: How To Increase Female Representation In ...mentioning
confidence: 99%
“…On this note, a recent publication demonstrated that from 669 studies published between 2017 and 2021 in six major sports medicine journals, only ca. 30% of studies included females as participants alongside males 141 . In addition, only ca.…”
Section: Future Considerations For Ms In Sesmentioning
confidence: 99%